Formulation of metronidazole tablets containing hydroxypropylated white yam (Dioscorea rotundata) starch as binding agent - Oluwatoyin Odeku (Journal of Excipients and Food Chemicals, 2017)
White yam starch obtained from the tubers of Dioscorea rotundata Poir was modified by hydroxypropylation and employed as a binding agent in metronidazole tablet formulation in comparison with corn starch BP. The quantitative effects of the novel starch binder on the mechanical (tensile strength and friability) and release properties (disintegration and dissolution times) of the metronidazole tablet has been analyzed using a full 23 factorial experimental design. The individual and interaction effects of type of starch binder (X1), concentration of binder (X2) and relative density (X3) on tensile strength, friability, disintegration time and dissolution time (t90) were determined. The ranking of the coefficients was X3 > X2 > X1 on T, X1 > X3 > X2 on F and X3 > X1 > X2 on DT and t90 (time for 90% drug release) indicating that the formulation variables influence the properties of metronidazole tablets to varying degrees. This indicates that the type and concentration of starch binder as well as the compression pressure employed in table formulation need to be carefully selected to obtain tablets with the desired mechanical and drug release properties. Hydroxypropyl white yam starch could be more useful as a binder especially when tablets with high mechanical strength but faster drug release properties is desired.